Coffee Consumption and Cardiovascular Diseases – Has the Time Come to Change Dietary Advice? A Mini Review - Wierzejska Regina (Polish Journal of Food and Nutrition Sciences)
The question whether coffee has a negative or a positive impact on human health has been the topic of much heated debate for years. Nevertheless, recent studies have not only failed to confirm earlier concerns, but in fact suggested a positive effect of coffee intake. Latest studies revealed that people who drink at least 3 cups of coffee per day are at a lower risk for type 2 diabetes, as well as liver and colon cancer. The reports on a possible correlation between coffee drinking and heart diseases have also generated optimistic results. No adverse associations between coffee consumption and coronary heart disease, stroke, and hypertension have been found. What is more, some authors demonstrated that coffee drinking may prevent cardiovascular diseases. Composition of coffee is determined by the strength of the brew and brewing methods. Unfiltered coffee is rich in cholesterol-raising diterpenes, therefore patients with dyslipidemia should be advised to drink filtered rather than non-filtered coffee. On the other hand coffee contains polyphenols which act as antioxidants, and these compounds are probably responsible for the suggested beneficial effect of coffee on health. This article summarizes the current literature reports on this controversial topic.